2022
DOI: 10.1101/2022.09.03.506485
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adenovirus 14p1 induced changes in miRNA expression increases lung immunopathogenesis

Abstract: Adenovirus is a frequent cause of mild, usually self-limited infections in infants and young children. Severe infections occur in immunocompromised patients but are rarely observed in healthy, immunocompetent adults. However, there have been outbreaks around the world of infections with different adenoviral (Ad) serotypes that have resulted in acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) in some of those infected. Ad14p1, the predominant circulating strain of Ad14 worldwide is one suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…We have reported that immunocompetent Syrian hamsters are permissive for HAdV-14 and HAdV-14p1 infection and that 14p1 infection results in patchy bronchopneumonia in the hamster, in contrast to the minimal lung inflammatory response to infection with the prototype HAdV-14 strain [32 ▪ ]. Additional studies showed that that the lung pathogenesis induced in hamsters by 14p1 is similar to the pathogenesis observed in humans, including increased inflammation as a result of immune cell infiltration and increased cytokine expression in the lungs of 14p1 vs HAdV-14 infected hamsters [33 ▪ ,47 ▪ ]. While none of the 14p1 infected Syrian hamsters died with the infectious doses used in our studies, 14p1 infection induced the early inflammatory responses during ALI that could allow progression to ARDS.…”
Section: Human Adenovirus-14p1 As a Model System For Virus-induced Ac...mentioning
confidence: 89%
See 1 more Smart Citation
“…We have reported that immunocompetent Syrian hamsters are permissive for HAdV-14 and HAdV-14p1 infection and that 14p1 infection results in patchy bronchopneumonia in the hamster, in contrast to the minimal lung inflammatory response to infection with the prototype HAdV-14 strain [32 ▪ ]. Additional studies showed that that the lung pathogenesis induced in hamsters by 14p1 is similar to the pathogenesis observed in humans, including increased inflammation as a result of immune cell infiltration and increased cytokine expression in the lungs of 14p1 vs HAdV-14 infected hamsters [33 ▪ ,47 ▪ ]. While none of the 14p1 infected Syrian hamsters died with the infectious doses used in our studies, 14p1 infection induced the early inflammatory responses during ALI that could allow progression to ARDS.…”
Section: Human Adenovirus-14p1 As a Model System For Virus-induced Ac...mentioning
confidence: 89%
“…This loss-of-function activity of HAdV-14p1 could be responsible for driving continued M1 polarization in the lungs of Ad14p1 infected individuals, allowing increased ALI and progression to ARDS. Recently, we have shown that cell corpses infected with the prototype HAdV-14 strain contain cellular microRNAs (miRNAs) that repress signal transduction pathways that would otherwise lead to the activation of pro-inflammatory cytokine expression [33 ▪ ]. Conversely, cell corpses infected with the HAdV14-p1 outbreak strain are not enriched in these same repressive miRNAs.…”
Section: Human Adenovirus-14p1 As a Model System For Virus-induced Ac...mentioning
confidence: 99%